Donald Trump’s Administration Confronting Missile Defence: Key Challenges and Probabilistic Overview - Nycz, Grzegorz (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
The text describes main US missile defence efforts in the first years of D. Trump’s administration. The analysis of current aspects of BMD (Ballistic Missile Defence) deployments is enhanced by probability analysis examining missile defence reliability. Donald Trump took office in the time of increased military competition between the West and Russia and a dangerous regional crisis related to North Korean nuclear arsenal and its ballistic tests. BMD appeared to bring additional chances to US deterrence options in regional scale, allowing more successful first strike or active defence posture. Notably, D. Trump’s administration managed to raise defence expenditures including BMD spending.